Involvement of the Wnt/β-Catenin Signaling Pathway in the Cellular and Molecular Mechanisms of Fibrosis in Endometriosis - Matsuzaki, Sachiko; Darcha, Claude (PLOS ONE, 2013)
BackgroundDuring the development and progression of endometriotic lesions, excess fibrosis may lead to scarring, chronic pain, and altered tissue function. However, the cellular and molecular mechanisms of fibrosis in endometriosis remain to be clarified. ObjectivesThe objective of the present study was to investigate whether the Wnt/β-catenin signaling pathway was involved in regulating the cellular and molecular mechanisms of fibrosis in endometriosis in vitro and to evaluate whether fibrosis could be prevented by targeting the Wnt/β-catenin pathway in a xenograft model of endometriosis in immunodeficient nude mice. MethodsSeventy patients (40 with and 30 without endometriosis) with normal menstrual cycles were recruited. In vitro effects of small-molecule antagonists of the Tcf/β-catenin complex (PKF 115-584 and CGP049090) on fibrotic markers (alpha smooth muscle actin, type I collagen, connective tissue growth factor, fibronectin) and collagen gel contraction were evaluated in endometrial and endometriotic stromal cells from patients with endometriosis. In vitro effects of activation of the Wnt/β-catenin signaling pathway by treatment with recombinant Wnt3a on profibrotic responses were evaluated in endometrial stromal cells of patients without endometriosis. The effects of CGP049090 treatment on the fibrosis of endometriotic implants were evaluated in a xenograft model of endometriosis in immunodeficient nude mice. ResultsTreatment with PKF 115-584 and CGP049090 significantly decreased the expression of alpha smooth muscle actin, type I collagen, connective tissue growth factor and fibronectin mRNAs in both endometriotic and endometrial stromal cells with or without transforming growth factor-β1 stimulation. Both endometriotic and endometrial stromal cell-mediated contraction of collagen gels was significantly decreased by treatment with PKF 115-584 and CGP049090 as compared to that of untreated cells. The animal experiments showed that CGP049090 prevented the progression of fibrosis and reversed established fibrosis in endometriosis. ConclusionAberrant activation of the Wnt/β-catenin pathway may be involved in mediating fibrogenesis in endometriosis.